Factores de riesgo laborales del personal profesional de Enfermería del Hospital General Manuel Ygnacio Monteros - Zona 7, periodo abril - septiembre 2022 - Chamba Poma, Priscila Stefania (2023)
Nursing professionals in the hospital environment perform functions that represent a high exposure to biological, physical, chemical, ergonomic, and psychosocial risks. The objective of this research was to identify occupational risk factors of the professional nursing staff of the General Hospital Manuel Ygnacio Monteros Zone 7, so that a descriptive, non-experimental, crosssectional, quantitative approach study was conducted, and a sample of 124 participants was considered, which were obtained through the simple random probability sampling technique and a questionnaire called "Occupational risks in nursing staff" was used as an instrument, based on the matrix of occupational risks of the Ministry of Labor Relations of Ecuador, which was modified for this research. The tabulation process was carried out using Word and SPSS version 22.0 programs. In terms of results, 100% of participants are exposed to biological risk factors, these are established like body fluids and contaminated material, while in chemical risks 95.2% are exposed to chlorhexidine and 100% are unprotected from alcohol gel and alcohol antiseptic. In relation to physical-mechanical risk factors, 100% are exposed to handling sharp instruments and annoying noises; on the other hand, in ergonomic risk factors, 100% of people have been exposed to handling loads and repetitive movements, and 99.2% of them to forced postures. Regarding psychosocial risk factors, 96.8% responded that they work under pressure and 76.6% have been demotivated in their work environment. In conclusion, nursing professionals are constantly exposed to multiple factors associated with occupational hazards, thus this research revealed that there is a prevalence of these risks, which can trigger diseases